Multifunctional Curcumin Mediate Multitherapeutic Effects. Issue 9 (3rd August 2017) - Shehzad, Adeeb; Qureshi, Munibah; Anwar, Muhammad Nabeel; Lee, Young Sup
Abstract: Inflammation can promote the development of arthritis, obesity, cardiovascular, type II diabetes, pancreatitis, metabolic and neurodegenerative diseases, and certain types of cancer. Compounds isolated from plants have been practiced since ancient times for curing various ailments including inflammatory disorders and to support normal physiological functions. Curcumin (diferuloylmethane) is a yellow coloring agent, extracted from turmeric that has been used for the prevention and treatment of various inflammatory diseases. Numerous studies have shown that curcumin modulate multiple molecular targets and can be translated to the clinics for multiple therapeutic processes. There is compelling evidence that curcumin can block cell proliferation, invasion, and angiogenesis as well as reduced the prolonged survival of cancer cells. Curcumin mediates anti‐inflammatory effect through downregulation of inflammatory cytokines, transcription factors, protein kinases, and enzymes that promote inflammation and development of chronic diseases. In addition, curcumin induces apoptosis through mitochondrial and receptor‐mediated pathways by activating caspase cascades. Curcumin is a safe and nontoxic drug that has been reported to be well tolerated. Available clinical trials support the potential role of curcumin for treatment of various inflammatory disorders. However, curcumin's efficacy is hindered by poor absorption and low bioavailability, which limit its translation into clinics. This review outlines the potential pharmacological and clinical role of curcumin, which provide a gateway for the beneficial role of plant isolated compounds in treatment of various inflammatory diseases and cancer.